An Empirical Analysis of Herding Behaviour in The US Mutual Funds Industry - Bui, Phuong Tram (2018)
The paper explores the existence of herding behaviour in the US mutual funds industry by utilising the methodology of cross-sectional dispersion in fund returns with respect to market return. We employ monthly return data of mutual funds from December, 2007 to December, 2017. In general, we find no evidence of herding towards the market consensus during periods of extreme price movements. Instead, we provide significant evidence of adverse herding behaviour where fund managers flock together around subsets of assets and ignore the market signals. No evidence of market-wide herding is found across different groups of investment objectives. The results suggest that balanced, growth and international funds exhibit significantly adverse herding behaviour. Moreover, large-sized funds are more likely to follow each other when trading than smaller-sized funds. Concerning herding asymmetry based on market return conditions, fund managers strongly engage in adverse herding behaviour during market upturns. In contrast, when the market is falling, the results are mixed: Growth, and growth & income funds show strong tendency to herd towards the market, while no evidence of herding is found in aggressive growth as well as emerging market funds. In particular, the global financial crisis (2007-2008) witnessed severe herding formation around the market movement for the whole sample, except for balanced, growth and international funds.